A Highly Pathogenic H5N1 Influenza A Virus Isolated from a Flamingo on the Caspian Sea Shore - Karamendin, Kobey (Microbiol Resour Announc, 2020)
In 2015, in the Kazakh part of the northern Caspian Sea region, during the monitoring of wild birds for avian influenza viruses, a highly pathogenic A/flamingo/Mangistau/6570/2015(H5N1) influenza virus was isolated from a dead flamingo. This study aimed to obtain the complete genome sequence of the isolate.